Concentration of secretory sIgA immunoglobulin in saliva of patients following surgical extraction of lower third molar and application of a cycle of laser biostimulation treatments - Szczerba-Gwóźdź, Joanna; Rahnama, Mansur; Jakiel, Joanna (Journal of Stomatology, 2016)
Introduction. Laser biostimulation through photobiochemical phenomena occurring on the molecular and enzymatic level of cells, determined as primary processes, induces secondary effects including analgesic, anti-inflammatory and anti-edematic reactions, as well as healing and regenerative action. On account of these properties the light of the biostimulating laser is used in the treatment and prevention of many stomatopathies. Aim of the study. To present the findings of the secretory sIgA immunoglobulin concentration in the saliva of patients after the surgical extraction of the lower third molar and application of four treatments of laser biostimulation. Methods. The evaluation of the sIgA concentration was carried out using ELISA immuno- assay method in forty generally healthy patients after extraction and another forty from the control group, in whom no dental treatment was undertaken. Saliva from patients was collected twice, first, before the extraction, second, after the fourth laser biostimulation treatment. Results. The analysis of the results showed the increase in the sIgA concentration in saliva after using biostimulating laser (96.31 mg/dl) when compared with that before treatment (86.36 mg/dl). Differences of sIgA concentration between two measurements were not statistically substantial. However, a statistically significant increase in the sIgA concentration in saliva of males after treatment (121.78 mg/dl) in comparison with that before biostimulation (83.21 mg/dl) (p=0.03) was stated. In saliva of women, the sIgA concentration was slightly lower after the laser treatment (81.02 mg/dl) comparing with that before biostimulation application (88.24 mg/dl). Conclusions. Local biostimulating laser application after the extraction of the lower third molar induces the increase in the concentration of the secretory sIgA immunoglobulin in patients’ saliva.